Militant or Non-State Armed Groups (NSAGs) During/After The Resolution of The Bakassi Conflict - Stephen Achuo Kpwa (Jurnal Pemerintahan dan Kebijakan (JPK), 2023)
The Bakassi peninsula conflict and its resolution had absorbed most of Cameroon and Nigeria's socio-political and economic oxygen and the international community in the 80s, 90s, and the first decade of the 21st century. Following military clashes between Cameroon and Nigeria over the peninsula, the conflict was finally resolved through the International Court of Justice (ICJ) verdict in 2002 and the Green Tree Agreement (GTA) 2006. The main thrust of this paper is to examine some militant or Non-State Armed Groups (NSAGs) that operated during and after the resolution of the Bakassi conflict. This paper also aims to examine the reasons why these NSAGs emerged briefly. This paper applied the qualitative research method and, from it, historical consolidation, content analyses and case studies. The study's results revealed seven prominent NSAGs that emerged during/after the resolution of the Bakassi conflict. The ICJ verdict of 2002 and the GTA of 2006 were one of prominent reasons why these NSAGs emerged. The study also found that the desire to control the area's natural resources, fight against Cameroon gendarme brutality, and the poor resettlement of the Bakassi returnees also served as springboards for the emergence of these NSAGs. Through its recommendations, this paper will help the Cameroon government redefine its policies toward ensuring and maintaining lasting peace in the Bakassi peninsula- understanding the reason for the emergence of the NSAGs, its trends, and how best to handle them.